2016
DOI: 10.1038/onc.2016.100
|View full text |Cite
|
Sign up to set email alerts
|

SHP-2-upregulated ZEB1 is important for PDGFRα-driven glioma epithelial–mesenchymal transition and invasion in mice and humans

Abstract: Gliomas are highly malignant brain tumors that are highly invasive and resistant to conventional therapy. Receptor tyrosine kinases (RTKs) such as PDGFRα (platelet-derived growth factor receptor-α), which show frequent aberrant activation in gliomas, are associated with a process of epithelial–mesenchymal transition (EMT), a cellular alteration that confers a more invasive and drug-resistant phenotype. Although this phenomenon is well documented in human cancers, the processes by which RTKs including PDGFRα me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 47 publications
5
60
0
Order By: Relevance
“…ZEB-1 and PDGFRa were found to be co-expressed in tissue samples from GBM patients, while high expression of both ZEB-1 and activated PDGFRa was identified to significantly coincide with poor survival. The same study further established Protein Tyrosine Phosphatase/Nonreceptor type (PTPN)-1 as a regulator of ZEB-1-induced and PDGFR-induced EMT in glioma (170). EMT may also be directly promoted by the microenvironment of GBM.…”
Section: Twist Snail Slug and Zebmentioning
confidence: 86%
“…ZEB-1 and PDGFRa were found to be co-expressed in tissue samples from GBM patients, while high expression of both ZEB-1 and activated PDGFRa was identified to significantly coincide with poor survival. The same study further established Protein Tyrosine Phosphatase/Nonreceptor type (PTPN)-1 as a regulator of ZEB-1-induced and PDGFR-induced EMT in glioma (170). EMT may also be directly promoted by the microenvironment of GBM.…”
Section: Twist Snail Slug and Zebmentioning
confidence: 86%
“…Some transcriptional factors could bind to the promoter region of E-Cadherin to suppress its expression, and further trigger the EMT conversion and metastasis of tumor cells, including SNAIL, SLUG, ZEB1 and ZEB2 [33, 34]. Among them, ZEB1 (characterized by the presence of 2 zinc finger clusters) is a well investigated transcriptional factor to act as a driver of EMT and cancer progression toward metastasis and invasion [35]. In our study, we have recognized ZEB1 as a downstream protein of PIK3R3 by evaluating the correlation between above-mentioned transcriptional factors and PIK3R3 expression based on the data obtained from TCGA, and assessing their expression in stable PIK3R3 overexpression and knockdown cells.…”
Section: Discussionmentioning
confidence: 99%
“…ZEB1 is an inducer of EMT. Zhang et al suggested that the regulation of ZEB1 by SHP2 is critical for PDGFA/PDGFRα signaling in the driving of EMT, cell migration, and invasion in glioma . In contrast, when we knocked down β‐catenin with siRNAs, EMT was reversed, and the migration of CRC cells was inhibited.…”
Section: Discussionmentioning
confidence: 88%